ANALYSIS ON CONVERSATIONAL IMPLICATURE OF THE GUEST STAR AND HOST AT THE DREW BARRYMORE TALK SHOW - Igna Mariana Purba; Melda Veby Ristella Munthe; Novra Melisa P. Hutabarat (RADJA PUBLIKA, 2025)
This research aimed to analyze conversations containing conversational implicature in the interactions between the host and guests on The Drew Barrymore Talk Show, using Grice’s (1975) theory of conversational implicature, which explains that conversational implicature is divided into two types: Generalized conversational implicature and Particularized conversational implicature. Implicature refers to utterances spoken by the speaker that are not meant literally. In conducting the research, the author used a descriptive qualitative method to present data in the form of descriptions and to identify conversational implicature. The data were obtained from conversation transcripts, which were then validated and matched repeatedly with videos from The Drew Barrymore Show’s YouTube channel. The data were summarized by analyzing conversations containing conversational implicature, then the selected data were classified into two types of conversational implicature. The data were further analyzed to determine the actual meaning contained in the implicit utterances and the speaker’s purpose in delivering those utterances. After analyzing the conversations in The Drew Barrymore Talk Show, the author found 35 instances of conversational implicature. Among these data, 19 were classified as generalized conversational implicature and 16 as particularized conversational implicature. In analyzing the actual meaning of these utterances, the researcher identified 9 types of purposes for using conversational implicature, namely: 15 for giving information, 6 for humor and jokes, 6 for lack of specific information, 2 for giving satire, 2 for self-protection, 1 for giving praise, 1 for politeness, 1 for giving support, and 1 for expressing happiness. Based on research findings, the use of conversational implicature in the from of generalized conversational implicature was dominantly applied in general or casual conversations. its purposes were not only to provide information and create humor but also varied depending on how the speaker delivered the utterance and the context in which it was used.